2012
DOI: 10.1007/s10964-012-9878-0
|View full text |Cite
|
Sign up to set email alerts
|

Linking Social Anxiety and Adolescent Romantic Relationship Functioning: Indirect Effects and the Importance of Peers

Abstract: Peer relationships undergo dramatic shifts in form and function during adolescence, at the same time the incidence of socially evaluative fears sharply rises. Despite well-established links between social anxiety and broader interpersonal functioning, there is a dearth of research evaluating the impact of social anxiety on functioning in close relationships during this developmental stage. The present study examines the impact of social anxiety on functioning in close friendships and romantic relationships dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…Adolescence is an important stage in one’s physical, psychological and social development. Because of the increase in the frequency and importance of peer interactions, adolescents are vulnerable to SAD and fear evaluation [ 13 ]. Empirical studies in various cultural contexts have shown that the correlation coefficients between the scores of the BFNE and SAD assessed by different instruments are always high [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence is an important stage in one’s physical, psychological and social development. Because of the increase in the frequency and importance of peer interactions, adolescents are vulnerable to SAD and fear evaluation [ 13 ]. Empirical studies in various cultural contexts have shown that the correlation coefficients between the scores of the BFNE and SAD assessed by different instruments are always high [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…These symptoms tend to make socially anxious individuals particularly conspicuous in social settings and not very popular with other people. Indeed, studies on normative adolescent samples have shown that higher levels of social anxiety are associated with lower peer acceptance (Erath, Flanagan, Bierman, & Tu, ; Flanagan, Erath, & Bierman, ; La Greca & Harrison, ; La Greca & Lopez, ) as well as increased peer victimization (Siegel, La Greca, & Harrison, ; Storch, Brassard, & Masia‐Warner, ), impairment in romantic relationships (Hebert, Fales, Nangle, Papadakis, & Grover, ), high levels of loneliness (Stoeckli, ), and poorer relationships with parents (Van Zalk & Kerr, ). Nonetheless, even though social anxiety is typically seen as a stable trait (Hayward et al., ), the experience and the consequences of social anxiety can vary from one individual to another.…”
mentioning
confidence: 99%
“…These results highlight the importance of the friend's network in the construction of romantic relationships in adolescence since adolescents seem to use this network as an environment conducive to their first romantic interactions. In this way, the idea conveyed in the international literature regarding the facilitating role of the peer group in romantic involvement, by enabling socialization in the romantic role and promoting behaviors and thoughts in this context, is confirmed (Hebert et al, 2013).…”
Section: Resultsmentioning
confidence: 61%
“…According to Hebert, Fales, Nangle, Papadakis, & Grover (2013), in the relationships of friendship, the adolescents find a space in which they can develop the social skills necessary for success in other contexts with peers, such as romantic relationships.…”
Section: Introductionmentioning
confidence: 99%